Patchy distributions of myelin and vesicular glutamate transporter 2 align with cytochrome oxidase blobs and interblobs in the superficial layers of the primary visual cortex - Rockoff EC; Balaram P; Kaas JH (Eye and Brain, 2014)
Emily C Rockoff,1 Pooja Balaram,1 Jon H Kaas1,2 1Department of Psychology, 2Department of Cell and Molecular Biology, Vanderbilt University, Nashville, TN, USA Abstract: Blobs are a modular component of the primary visual cortex (area 17) of all primates, but not of other mammals closely related to primates. They are characterized as an even distribution of patches, puffs, or blobs of dense cytochrome oxidase (CO) expression in layer III of area 17, and are now known to differ from surrounding, nonblob cortex in thalamic, intrinsic, and extrastriate connections. Previous studies have also recognized a blob-like pattern of myelin-dense patches in layer III of area 17 of primates, and more recently the vesicular glutamate transporter (VGLUT)-2 isoform of the VGLUT family has been found to selectively distribute to layer III patches in a similar blob-like pattern. Here, we sought to determine if the blob-like patterns all identify the same modular structures in area 17 of primates by staining alternate brain sections cut parallel to the surface of area 17 of a prosimian primate (Otolemur garnettii) for CO, myelin, and VGLUT2. By aligning the sections from the three preparations, we provide clear evidence that the three preparations all identify the same modular blob structures. The results provide a further understanding of the functional nature of the blobs by demonstrating that their higher level of CO activity is related to thalamic inputs from the lateral geniculate nucleus that use VGLUT2 as their main glutamate transporter, and via myelinated axons. Keywords: columns, modules, visual cortex, primates, prosimians